BAY LEAVES INFUSE MAINTAIN THE QUALITY AND DURABILITY OF BALI BEEF - Suada, I Ketut; Purnama, Dimas Indra Dwi; Agustina, Kadek Karang (Buletin Veteriner Udayana, 2018)
Bay leaf (Syzygium polyanthum) is often used in a variety of dishes to enhance the flavor, without realizing that the leaves contain antimicrobial compounds are bactericidal. The purpose of this study was to determine the effect of immersion bay leaves infuse to the quality and durability of beef bali at room temperature laying in terms of odor, color, texture, pH, water content and water holding capacity. Test colors using a color standard ISO beef concluded by the ten panelists, test smells and textures using ten panelists, test the pH was measured using a pH meter, test the water content carried by the drying method using the oven, the next test of water holding capacity using methods Hamm. The results showed that soaking treatment bay leaf infusion with concentration (0%, 5%, 10% and 15%) was highly significant to the smell, color, and texture of beef bali, old laying on the temperature the room was highly significant on pH and water content of beef bali but did not significantly affect water holding capacity. Can be concluded that the quality and endurance of bali beef can maintained by marinated into bay leaves infuse.